1999
DOI: 10.1093/carcin/20.6.1011
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention by curcumin during the promotion stage of tumorigenesis of mammary gland in rats irradiated with gamma-rays

Abstract: We have evaluated the chemopreventive effects of curcumin on diethylstilbestrol (DES)-induced tumor promotion of rat mammary glands initiated with radiation. Sixty-four pregnant rats received whole body irradiation with 2.6 Gy γ-rays from a 60 Co source at day 20 of pregnancy and were divided into two groups after weaning. In the control group of 39 rats fed a basal diet and then implanted with a DES pellet for 1 year, 33 (84.6%) developed mammary tumors. Twenty-five rats were fed diet containing 1% curcumin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(41 citation statements)
references
References 60 publications
0
41
0
Order By: Relevance
“…DISCUSSION Curcumin has been shown to have chemopreventive effects on breast cancer. 20,21 Recently, Inano et al have reported that curcumin has a potent preventive activity during the DES-dependent promotion stage of radiation-induced mammary tumorigenesis. 20 In our study, we provide evidence that curcumin exerts multiple different suppressive effects on human breast carcinoma cells in vitro.…”
Section: Curcumin's Modulation Of Angiogenesis Factor Expressionmentioning
confidence: 99%
“…DISCUSSION Curcumin has been shown to have chemopreventive effects on breast cancer. 20,21 Recently, Inano et al have reported that curcumin has a potent preventive activity during the DES-dependent promotion stage of radiation-induced mammary tumorigenesis. 20 In our study, we provide evidence that curcumin exerts multiple different suppressive effects on human breast carcinoma cells in vitro.…”
Section: Curcumin's Modulation Of Angiogenesis Factor Expressionmentioning
confidence: 99%
“…In each experiment, 100 µL aliquots of growth medium, containing exponentially growing cells, were placed into 96-well plates, at 1.0 × 10 5 cells per well, then incubated for 24 hours. Subsequently, HepG2 cells were incubated with various formulations of curcumin (at concentrations of 0, 4,6,8,10,12,16, and 20 µΜ, with eight wells per concentration). After 48 hours of incubation, MTT solution (5 mg/mL) was added to each well.…”
Section: Mtt Assaymentioning
confidence: 99%
“…It is of particular interest to note that Curcuma longa L is a fungus and fungi are well known for their high copper content. Since 13-diketones are well known chelating agents [123,124] and this fully conjugated [5- [126] reported that feeding Curcumin decreased the incidence of marnmm3' tumor m rats. A 1% Curcumin diet fed to 2.6 Gy whole-body irradiated pregnant Wistar-MS rats just prior to pup birth (a mammary tumor imtiating procedure) and then implanted with diethylstilbestrol sustained release pellets for 12 mo following weaning (a mammary tumor promoter regimen) caused a dramatically decreased incidence of mammary tumor.…”
Section: Chemical Consequences Of Ionizing Radiationmentioning
confidence: 99%